Scalable bio-friendly method for production of homogeneous metal oxide nanoparticles using green bovine skin gelatin - Alnarabiji, M.S. (Elsevier Ltd, 2017)
The use of bovine skin gelatin in the synthesis of variety of nanostructures is a bio-friendly approach. In the current study, we investigated experimentally, for the first time, scalable process for production of homogeneous hexagonal zinc oxide nanoparticles (ZnO-NPs) not only with narrow size distribution and simple process but also cost effective and bio-friendly by green sol-gel method utilizing bovine skin gelatin (BSGB) matrix. Statistical analysis was done to evaluate the reliability of measuring the particle size using X-ray Diffraction analysis (XRD) and/or surface area (BET) instead of High Resolution Transmission Electron Microscope (HRTEM) and the following novel points are found. Impressively monodispersed ZnO-NPs with hexagonal structure were synthesized by adjusting the pH. All the samples exhibited hexagonal (wurtzite) crystal shape while the obtained morphology of the particles varies from hexagonal NPs to combination of hexagonal NPs and rod-like particles with reducing the pH from 6 to 2 due to the variation of bloom strength of the gelatin. Long chain gelatin contributed to suppressing the growth of nanoparticle and controlling the morphology. We discovered statistically that there was insignificant difference in measuring the particle size using XRD and HRTEM which can save time, energy, and cost at industrial aspect. © 2017 Elsevier Ltd